Application and Feasibility of the Soviet Armenian Experience in Integrating Repatriates in the Republic of Armenia - Makaryan, Lilit (History and Culture, 2025)
The first caravans of Armenian emigrants who survived the Genocide and settled in foreign countries arrived in Soviet Armenia in 1921-1922. The first successful attempt at repatriation was organized from 1921 to 1936. The authorities of Soviet Armenia spared no effort in accepting, settling, providing housing, employment, and education to the immigrating compatriots, as well as integrating them into society. To organize the immigration process, raise the prestige of Soviet Armenia in the Diaspora, and strengthen ties with the homeland, state structures were established under the government during the Soviet period, fully engaged in pro-patriotic work. Through our research, we have presented the successful experience of organizing repatriation and integration during the Soviet period, highlighting their applicability and feasibility in the Republic of Armenia. We have also identified the factors hindering these efforts through a survey.